Impact of astaxanthin supplementation on markers of cardiometabolic health and tactical performance among firefighters - Drew E. Gonzalez; Broderick L. Dickerson; Sarah E. Johnson; Kathryn E. Woodruff; Megan Leonard; Choongsung Yoo; Joungbo Ko; Dante Xing; Victoria Martinez; Jacob Kendra; Landry Estes; Ryan J. Sowinski; et al. (Taylor & Francis Group, 2024)
Rationale Firefighters are at risk for cardiovascular disease due to occupational-related inflammation, oxidative stress, and lifestyle practices. Astaxanthin (AX) possesses anti-inflammatory/antioxidant and purported ergogenic properties. This study examined the impact of supplementing the diet with 12 mg/d AX for four weeks on markers of inflammation, oxidative stress, cardiometabolic health, exercise capacity, and occupation-related performance in career firefighters.Methods In a randomized, double-blinded, placebo-controlled, crossover fashion, 15 male career firefighters (34.5 ± 7.4 years; 177.7 ± 7.0 cm; 95.6 ± 12.0 kg; 30.1 ± 2.9 kg/m2; 11.03 ± 6.85 years of service) ingested 12 mg/d of AX (AstaReal®, AstaReal AB, Nacka, SWE) or placebo (PLA) for four weeks while following a standardized resistance training program. After each treatment, testing sessions were completed to assess inflammatory markers, oxidative stress markers, cardiopulmonary exercise capacity, and performance to a fire ground test (FGT) consisting of nine fire suppressive activities. Data were analyzed using general linear model (GLM) analysis with repeated measures. Clinical significance was assessed via mean changes from baseline with 95% confidence intervals.Results Analysis of mean percent changes from baseline revealed that AX supplementation lessened the inflammatory response to to performing an incremental maximal exercise test and attenuated increases in interleukin-1β, cortisol, and uric acid in response to performing fire suppressive activities compared to when they ingested PLA. However, most of these effects were within groups rather than between groups. Additionally, there was evidence that AX ingestion increased the ventilatory anaerobic threshold. Four weeks of AX supplementation did not significantly affect fasting markers of oxidative stress, blood lipids, performance during the FGT, general clinical chemistry panels, or self-reported side effects.Conclusions Results provide some evidence that AX supplementation may help mediate occupation-related inflammation in response to high-intensity, short-duration exercise in firefighters. More research is warranted to determine if long-term supplementation can improve cardiometabolic risk in this population.Clinical trial registration ISRCTN10901752.